2021
DOI: 10.1587/transfun.2020kep0007
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Acceleration of the Quadratic Knapsack Problem on an Ising Machine

Abstract: The binary quadratic knapsack problem (QKP) aims at optimizing a quadratic cost function within a single knapsack. Its applications and difficulty make it appealing for various industrial fields. In this paper we present an efficient strategy to solve the problem by modeling it as an Ising spin model using an Ising machine to search for its ground state which translates to the optimal solution of the problem. Secondly, in order to facilitate the search, we propose a novel technique to visualize the landscape o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…They are NP-hard problems [17], [18]. It has been reported that existing Isingmachine hardware is unable to provide even a near-optimal solution of them [32], [33]. Section 5.2 shows the assignment process of {m i } and {s i } for each combinatorial optimization problem.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They are NP-hard problems [17], [18]. It has been reported that existing Isingmachine hardware is unable to provide even a near-optimal solution of them [32], [33]. Section 5.2 shows the assignment process of {m i } and {s i } for each combinatorial optimization problem.…”
Section: Resultsmentioning
confidence: 99%
“…where n item is the number of items. The matrix {p i,j } is referred to as the profit matrix [32]. The overall weight of items within the knapsack is given by…”
Section: Binary Quadratic Knapsack Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…This section first shows the experimental results of SA simulation for QUBO problems constructed using BE, UE, and HE for QKPs of different sizes and feature values. After that, utilizing well-known benchmark QKPs [22], we estimate the performance of HE on a solid-state annealer and compare it with the state-of-the-art results reported in [16].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we can utilize the formulation with QUBO as well as the Ising model. Various methods for formulating COPs as Ising models or QUBOs have been reported so far [14]- [16], and standard techniques have been established for some representative COPs [17].…”
Section: Introductionmentioning
confidence: 99%